Gambaran kasus diare pada anak di Rumah Sakit Ibnu Sina Makassar - An’nisa’a, Nurul Fadillah; Arfah, Arni Isnaini; Fattah, Nurfachanti; Darma, Sidrah; Rasfayanah, Rasfayanah; Puspitasari, Ayu (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Diarrhea is an increase in the water content of the stool due to an imbalance in the normal functioning of the physiological processes of the small and large intestine responsible for the absorption of various ions, other substrates, and consequently water. The main cause of death in diarrhea is dehydration which occurs due to loss of fluid and electrolytes through the stool. While other causes are dysentery, nutrition, and infection. Purpose: To determine the description of diarrhea cases in children at Ibnu Sina Hospital, Makassar. Method: Descriptive research with a cross-sectional approach to see the picture of diarrhea cases in children at Ibnu Sina Hospital, Makassar for the period January - December 2023. The data used are secondary data in the form of medical records and patient data recorded as many as 713 people. The sample used was 88 respondents with acute diarrhea. The sample size used in this study is in accordance with the Slovin formula, with the inclusion criteria of children aged 5-18 years who experience diarrhea, while the exclusion criteria are children who experience diarrhea accompanied by other diseases. Results: The majority of respondents aged 5-9 years were 47 people (53.4%). The distribution of gender between males and females was even, with 44 people (50.0%) being male and female. Most respondents had good nutritional status as many as 44 respondents (50%), the degree of dehydration was obtained as many as 42 (47.6%) without dehydration, and as many as 83 respondents (94.3%) were given zinc. Conclusion: The incidence of diarrhea in this study was 713 cases of diarrhea. Cases of diarrhea based on age in children were mostly in the 5-9 year age group, and there was no difference between genders. In addition, without dehydration or mild/moderate dehydration, good nutritional status, and zinc administration. Keywords: Case Description; Children; Diarrhea. Pendahuluan: Diare adalah peningkatan kandungan air dalam tinja karena ketidakseimbangan fungsi normal proses fisiologis usus kecil dan besar yang bertanggung jawab untuk penyerapan berbagai ion, substrat lain, dan akibatnya air. Penyebab utama kematian diare yaitu dehidrasi yang terjadi akibat kehilangan cairan dan elektrolit melalui feses. Sementara penyebab lainnya adalah disentri, gizi, dan infeksi. Tujuan: Untuk mengetahui Gambaran kasus diare pada anak di Rumah Sakit Ibnu Sina Makassar. Metode: Penelitian deskriptif melalui pendekatan cross sectional untuk melihat gambaran kasus diare pada anak di Rumah Sakit Ibnu Sina Makassar periode Januari – Desember 2023. Data yang digunakan adalah data sekunder berupa rekam medik dan ditemukan data pasien yang tercatat sebanyak 713. Sampel yang digunakan berjumlah 88 responden dengan kondisi diare akut. Besar sampel yang digunakan dalam penelitian ini adalah sesuai dengan rumus besar slovin, dengan kriteria inklusi anak usia 5-18 tahun yang mengalami diare, sedangkan kriteria eksklusinya adalah anak yang mengalami diare disertai penyakit lain. Hasil: Mayoritas 47 responden (53.4%) berada pada umur 5-9 tahun. Sebaran jenis kelamin antara laki-laki dan perempuan merata, sebanyak 44 (50.0%) laki-laki dan perempuan. Sebagian besar responden memiliki status gizi baik sebanyak 44 responden (50%), derajat dehidrasi didapatkan sebanyak 42 (47.6%) tanpa dehidrasi, dan sebanyak 83 responden (94.3%) diberikan zinc. Simpulan: Angka kejadian diare dalam penelitian ini sebanyak 713 kasus diare. Kasus diare berdasarkan umur pada anak paling banyak pada kelompok umur 5-9 tahun dan tidak ada perbedaan antara jenis kelamin. Selain itu, tanpa dehidrasi atau dehidrasi ringan/sedang, berstatus gizi baik, dan dilakukan pemberian zinc. Kata Kunci: Anak; Diare; Gambaran Kasus.